2019
DOI: 10.2166/wcc.2019.101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of soft computing and regression-based techniques for the estimation of evaporation

Abstract: The estimation of evaporation in the field as well as the regional level is required for the efficient planning and management of water resources. In the present study, artificial neural network (ANN) and multiple linear regression (MLR)-based models were developed to estimate the pan evaporation on the basis of one day-lagged rainfall (Pt−1), one day-lagged relative humidity (RHt−1), current day maximum temperature (Tmax) and minimum temperature (Tmin). These were selected as the most effective parameters on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…This assessment is based on pertinent studies in the literature. For instance, in a comparative study between the capability of machine learning versus ANN, and statistical technique versus MLR, for EP prediction, it was found that the model efficiency and correlation coefficient of the ANN was higher than the MLR model for the calibration and validation phases [20]. The same result has been noted for the superiority of ANFIS model over the MLR statistical model [74].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This assessment is based on pertinent studies in the literature. For instance, in a comparative study between the capability of machine learning versus ANN, and statistical technique versus MLR, for EP prediction, it was found that the model efficiency and correlation coefficient of the ANN was higher than the MLR model for the calibration and validation phases [20]. The same result has been noted for the superiority of ANFIS model over the MLR statistical model [74].…”
Section: Discussionmentioning
confidence: 57%
“…Similarly, data-driven approaches, including computational intelligence and machine learning are also suitable for estimating the EP. Recently, regular hybrid and integrative data-driven models (e.g., artificial neural networks (ANN) as well as support vector machine (SVM) and adaptive neuro-fuzzy inference systems (ANFIS)) have been used for estimating the EP [7,[12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study were compared with the previous studies conducted on modeling pan-evaporation using several artificial intelligence (AI) techniques optimized by bio-inspired algorithms (Kumar et al, 2021;Majhi et al, 2020;Qasem et al, 2019;Salih et al, 2019;Singh et al, 2021). The previous studies reported the effective utility of hybrid AI methods for pan-evaporation at different locations in varying climates through statistical metrics and visual investigation.…”
Section: Discussionmentioning
confidence: 97%
“…m n are the regression coefficients, and C is constant. MLR models were the usual method for estimating responses between a dependent variable and various independent factors where the dependent variable and independent variables had a linear connection [35].…”
Section: Multiple Linear Regressionmentioning
confidence: 99%